2021
DOI: 10.18621/eurj.774757
|View full text |Cite
|
Sign up to set email alerts
|

The perception concerning the COVID-19 pandemic: case of Turkey

Abstract: Objectives: This study aims to evaluate the level of knowledge and perception of the Turkish society about the COVID-19 pandemic. Methods: This cross-sectional study whose sampling consists of 903 adults. Results: About half (49.6%) of the participants' information sources about COVID-19 composed of printed and visual media tools such as television, radio, newspaper, etc. 57.5% of the participants stated that their selfknowledge levels about COVID-19 were at a good level, whereas 19.7% of them at a very good l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…There is no significant difference in satisfaction by gender. These results are similar to some other studies (Williems et al, 2020;Enria et al, 2020;Hoşgör et al, 2021). Although not in terms of satisfaction with the government's measures, it been found that older individuals are more satisfied with their situation than young people in studies that are evaluated in terms of life satisfaction in the COVID-19 period in general (Bizdan-Bluma et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is no significant difference in satisfaction by gender. These results are similar to some other studies (Williems et al, 2020;Enria et al, 2020;Hoşgör et al, 2021). Although not in terms of satisfaction with the government's measures, it been found that older individuals are more satisfied with their situation than young people in studies that are evaluated in terms of life satisfaction in the COVID-19 period in general (Bizdan-Bluma et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…One of the interesting findings of this study is that 53.5% of the participants in general are not satisfied with the COVID-19 measures of the WHO. In association with the level of trust in the scientific committee and WHO, in another study conducted for Turkey, similar results were obtained (Hoşgör et al, 2021). A study for the USA found that over 38% of individuals doubted WHO's ability to manage the pandemic, and 38% had some confidence.…”
Section: Discussionsupporting
confidence: 52%
“…In a study conducted in Nigeria during the pandemic, the most widely used sources of information regarding COVID-19 disease were traditional media, social media, internet, Nigeria Center for Disease Control, family / friends and political leaders respectively [ 12 ]. In a study conducted with 907 people in Turkey, the sources of information most trusted by individuals regarding COVID-19 were university / training-research hospitals in the city where they are located, the World Health Organization, and the Coronavirus Scientific Committee of the Ministry of Health of the Republic of Turkey respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease-2019 [Coronavirus Disease-2019 (COVID- 19)], in which the first case was detected in December 2019 in the city of Wuhan, China's Hubei province, is an infectious disease that caused the World Health Organization (WHO) to declare it a pandemic (1,2). The COVID-19 pandemic harms the lives, health and economy of individuals.…”
Section: Introductionmentioning
confidence: 99%